2001
DOI: 10.1177/002246690103500102
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Growth Indicators for Low-Achieving Students in Middle School Mathematics

Abstract: The purpose of this study was to explore the technical adequacy of potential indicators of growth in mathematics at the middle school level. Correlation and regression analyses were used to investigate the reliability and criterion validity of four measures in mathematics. One hundred students from a racially and socioeconomically diverse urban middle school completed 4 measures (1 involving basic facts and 3 involving estimation) twice in a 1-week period. Criterion measures included grades in school, standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
(40 reference statements)
1
42
1
Order By: Relevance
“…Two approaches are used to develop CBMs: curriculum sampling and robust indicators (Foegen & Deno, 2001;Fuchs, 2004). The curriculum sampling approach involves systematically sampling the content from the annual curriculum within a specific grade level (i.e., the content standards).…”
Section: Cbm Principles Guiding the Development Of The Egmamentioning
confidence: 99%
“…Two approaches are used to develop CBMs: curriculum sampling and robust indicators (Foegen & Deno, 2001;Fuchs, 2004). The curriculum sampling approach involves systematically sampling the content from the annual curriculum within a specific grade level (i.e., the content standards).…”
Section: Cbm Principles Guiding the Development Of The Egmamentioning
confidence: 99%
“…Computation and application aspects of mathematics, as used in CBM, have been shown to be highly related but represent distinct constructs (Thurber, Shinn, & Smolkowski, 2002). Basic fact fluency may represent a robust indictor of mathematics performance with utility for treatment planning (Christ, Scullin, Tolbize, & Jiban, 2008; Espin, Deno, Maruyama, & Cohen, 1989; Foegen, 2000; Foegen & Deno, 2001), albeit it is unlikely to be representative of general mathematics achievement (Christ et al, 2008). Computation fluency is considered the hallmark of mathematics learning disabilities (Gersten, Jordan, & Flojo, 2005), and neuroscientific evidence supports that fact fluency is associated with performance on higher level mathematics tasks (e.g., Price, Mazzocco, & Ansari, 2013).…”
Section: Technical Features Of Cbm Static Scores At the Secondary Levelmentioning
confidence: 99%
“…Robust indicators are selected to represent core competence and often require students to integrate a variety of concepts and skills taught in the curriculum. Some researchers have demonstrated that fluency with basic facts may serve as a robust indicator in the elementary and middle school grade levels (Espin, Deno, Maruyama, & Cohen, 1989;Foegen, 2000;Foegen & Deno, 2001). Whereas fluency with basic facts clearly is not representative of the full curriculum, it can serve as an efficient proxy of more global outcomes because of its correlations with other indicators of mathematics proficiency.…”
Section: Approaches To the Development Of Progress Monitoring Measuresmentioning
confidence: 99%